2016
DOI: 10.14390/jsshp.hrp2016-008
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal risk assessment of gestational hypertension and preeclampsia using clinical information

Abstract: Aim:To assess the risks of developing gestational hypertension (GH) and preeclampsia (PE) during pregnancy based on clinical information. ). The estimated risk ratios predicted subsequent GH and PE with sensitivities of 61.5% and 67.0%, and specificities of 67.0% and 64.4%, respectively. The areas under the receiver operating characteristic curves for GH and PE were 0.70 and 0.68, respectively. Conclusions:The estimated risk ratios determined in this study may identify women at high risk of GH or PE before dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…The current study revealed that DM and hypertension were the most significant risk factors among study participants diagnosed with PE. This was consistent with Shiozaki, et al [21] in Japan who found that DM in that study was one of the risk factors for developing PE. Additionally, a history of hypertension was a risk factor for PE in a previous study done by Bartsch,et al [22].…”
Section: Risk Factors Of Pe According To Nomogram Prediction Among Study Participantssupporting
confidence: 92%
“…The current study revealed that DM and hypertension were the most significant risk factors among study participants diagnosed with PE. This was consistent with Shiozaki, et al [21] in Japan who found that DM in that study was one of the risk factors for developing PE. Additionally, a history of hypertension was a risk factor for PE in a previous study done by Bartsch,et al [22].…”
Section: Risk Factors Of Pe According To Nomogram Prediction Among Study Participantssupporting
confidence: 92%